Exploring the Potential of ChatGPT in Improving Online Marketing and Promotion of MSMEs - Muhamad Malik Mutoffar; Sri Kuswayati; Fetty Tri Anggraeny; Tarsinah Sumarni (Jurnal Minfo Polgan, 2023)
In the ever-evolving digital era, the use of technology and the internet has changed the way businesses operate, including in product marketing and promotion. ChatGPT is allegedly an example of AI technology that can improve online marketing and promotion of MSMEs. This research will explore the potential of ChatGPT in improving online marketing and promotion of MSMEs. This research is qualitative in nature. The techniques used to obtain information involve careful observation and meticulous note-taking, followed by analytical procedures such as data reduction, visualisation, and inference. The study arrived at the conclusion that exploring the potential of ChatGPT in enhancing online marketing and promotion of MSMEs offers an exciting opportunity for MSMEs to reach potential customers, improve customer interactions, and optimise marketing efforts efficiently. With ChatGPT's ability to provide natural responses, provide product information, provide recommendations, and run marketing campaigns, MSMEs can expand their market reach and provide a better customer experience.